PV Solar Statcom to Improve Power Quality in Distribution System - Chougale Rajkumar Kundlik , Dr. P. Karpagavalli (International Journal of Advanced Science and Technology, 2020)
In this study we demonstrates grid-associated solar photovoltaic (PV) system with reactive power control as a STATCOM called as PV solar STATCOM. This research talks about the issues concerned to power quality for dispersed age systems dependent on sustainable power sources like solar energy. The study highlights a complete simulation, balance as well as modeling of grid connected PV module like evaluation of different problems associated with power quality are discussed and concluded. The power quality is substantially impacted by interconnection of unlimited sources of energy to the grid.